2012
DOI: 10.2172/1055601
|View full text |Cite
|
Sign up to set email alerts
|

Fukushima Daiichi accident study : status as of April 2012.

Abstract: In response to the accident at the Fukushima Daiichi nuclear power station in Japan, the U.S. Nuclear Regulatory Commission (NRC) and Department of Energy agreed to jointly sponsor an accident reconstruction study as a means of assessing severe accident modeling capability of the MELCOR code. MELCOR is the state-of-the-art system-level severe accident analysis code used by the NRC to provide information for its decision-making process in this area. The objectives of the project were: (1) collect, verify, and d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
121
0
4

Year Published

2013
2013
2021
2021

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 95 publications
(135 citation statements)
references
References 8 publications
4
121
0
4
Order By: Relevance
“…One such case study is a margins-based comparison of the behavior of Zircaloy cladding with new cladding designs based on silicon carbide (SiC). Zircaloy cladding works well under normal conditions, but it is well known that loss of core cooling can lead to core melt, with release of radioactive material into containment, as occurred at Three Mile Island in 1979 [2], and release of radioactive material from containment, as occurred at Fukushima in 2011 [3]. In addition to loss of the fuel cladding barrier in these accidents, a significant amount of combustible hydrogen was also produced, leading to additional damage and affecting the release of radioactive material at Fukushima.…”
Section: Rismc Pathway Backgroundmentioning
confidence: 99%
See 1 more Smart Citation
“…One such case study is a margins-based comparison of the behavior of Zircaloy cladding with new cladding designs based on silicon carbide (SiC). Zircaloy cladding works well under normal conditions, but it is well known that loss of core cooling can lead to core melt, with release of radioactive material into containment, as occurred at Three Mile Island in 1979 [2], and release of radioactive material from containment, as occurred at Fukushima in 2011 [3]. In addition to loss of the fuel cladding barrier in these accidents, a significant amount of combustible hydrogen was also produced, leading to additional damage and affecting the release of radioactive material at Fukushima.…”
Section: Rismc Pathway Backgroundmentioning
confidence: 99%
“…In addition, the research work has identified new phenomena, such as breakaway oxidation and oxygen diffusion from the cladding inside surfaces, which are believed to further adversely affect the fuel cladding embrittlement process. Thus, post quench ductility (which is necessary to ensure coolable core geometry) 3 is not guaranteed following a postulated LOCA. The proposed rule would establish new requirements for zirconium-based alloys to prevent breakaway oxidation and account for oxygen diffusion from the oxide fuel pellet during the operating life of the fuel.…”
Section: Recently-proposed Rulemaking On Regulatory Acceptance Criteriamentioning
confidence: 99%
“…SINCE the nuclear accident in Japan in 2011, [1,2] considerable research has been devoted to identify light water reactor (LWR) fuel systems that tolerate severe accident scenarios (i.e., beyond design basis accidents). [3][4][5][6][7][8][9] The objective is to provide larger safety margins, i.e., delay the onset of severe LWR core degradation by reducing the rate of H 2 and heat generated by the rapid oxidation of Zr-base alloy cladding and increase the coping time after an accident.…”
Section: Introductionmentioning
confidence: 99%
“…However, there seems to be large uncertainties among different codes (e.g., MELCOR, MAAP and SAMPSON) in predictions of RPV lower head failures [5][6][7]. In these system analysis codes, where phenomena associated with lower head failure are poorly understood, such as penetration failure, the models are very simple and parametric.…”
mentioning
confidence: 99%